Gut microbiota modify risk for dietary glycemia-induced age-related macular degeneration. (3rd September 2018) - Rowan, Sheldon; Taylor, Allen
ABSTRACT: Age-related macular degeneration (AMD) is a leading cause of blindness world-wide. Although the etiology of AMD is multifactorial, diet and nutrition have strong epidemiologic associations with disease onset and progression. Recent studies indicate a role for gut microbiota in development of AMD in mouse models and in some forms of human AMD. We previously found that consuming lower glycemia diets is associated with protection against AMD in humans and switching from higher to lower glycemia diets arrests AMD phenotypes in mice. Gut microbiota populations and circulating microbial cometabolites were altered in response to dietary carbohydrates, indicating a gut-retina axis. Here we explore additional gut microbiota-AMD interactions that point toward pathogenic roles for some gut microbiota families, including Ruminococcaceae and Lachnospiraceae, and individual members of Turicibacteraceae, Clostridiaceae, and Mogibacteriaceae. We also speculate on potential mechanisms by which gut microbiota influence AMD, with the objective of devising new AMD diagnoses and treatments.